CHANGES IN THE MICROSTRUCTURE OF SOLONETZES DURING IRRIGATION - T. Tursina; I. Lukyanov (Бюллетень Почвенного института им. В.В. Докучаева, 2011)
Changes in the microstructure of steppe and meadow-steppe solonetzes of the Caspian Sea, occupying flattened elevated micro-relief elements in the three-dimensional soil complex in the area of chestnut soils in the area of the Kislovskaya irrigation system, under the influence of irrigation on the background of planning and gypsum plastering are described. Loss of aggregated humus material during the planning of saline soils is the cause of low structural properties of irrigated saline soils. Their development requires the introduction of meliorants, changes in the microstructure of solonts during gypsum plastering are shown.